Marketing Mix Implementation to Increase Meeting Room Sales at The Jayakarta Lombok Beach Resort & Spa - Ari Asih Purnamawati Dewi; I Putu Astawa; I Ketut Suarja; Luh Eka Armoni; Made Sudiarta; Ni Nyoman Sri Astuti (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
Purpose: This research aims to determine the implementation of the marketing to the sales of meeting room in The Jayakarta Lombok Beach Resort & Spa. The problem outlined in this research is what strategy to do by the sales & marketing in increasing meeting room sales at The Jayakarta Lombok Beach Resort & Spa. Research methods: This research was conducted on the sales & marketing parties that is sales & marketing managers and sales executives at The Jayakarta Lombok Beach Resort & Spa. Analysis of the data used a qualitative descriptive analysis that elaborates information from the interviews and links with theories that support the discussion related to the marketing mix conducted by The Jayakarta Lombok Beach Resort & Spa. Results and discussion: The results obtained are the marketing mix strategy carried out at The Jayakarta Lombok Beach Resort & Spa, especially in the meeting section, which is quite good, but has a lack of promotion. The strategy implemented to increase sales are also quite effective. Implication: The development that can be done is to increase online and offline promotions and also keep communication between the sales team and consumers. Keywords: hotel, room sales, meeting room, marketing mix.